A Characterization of the Diffuse Galactic Emissions at Large Angular Scales Using the Tenerife Data. (11th March 2013) - Macías-Pérez, J. F.; Davies, R. D.; Watson, R.; Gutierrez, C. M.; Rebolo, R.
Abstract : The anomalous microwave emission (AME) has been proved to be an important component of the galactic diffuse emission in the range from 20 to 60 GHz. To discriminate between different models of AME, low frequency microwave data from 10 to 20 GHz are needed. We present here a reanalysis of published and unpublished Tenerife data from 10 to 33 GHz at large angular scales (from 5 to 15 degrees). We cross-correlate the Tenerife data to templates of the main galactic diffuse emissions: synchrotron, free-free, and thermal dust. We find evidence of dust-correlated emission in the Tenerife data that could be explained as spinning dust grain emission.